Comparative analysis of vertical green façades with movable panels from the perspective of their thermal performance and applicability in sustainable urban areas - Şık Seyrek Cansu Iraz; Widera Barbara (Lodz University of Technology Press, 2023)
The positive effects of urban green spaces on both the health of city residents and urban ecosystems cannot be denied. Green urban spaces help prevent environmental problems such as air pollution, urban heat island effect and are necessary for citizens to socialize, appreciate nature and foster a healthier society. However, with the urban tissue densification, decrease is observed in the amount of green urban areas. During the revitalization process, in order to create inclusive and sustainable cities, it is important to design alternative green public spaces. We argue that vertical green façade systems can be used as one of the most effective options for active interaction between the residents and nature. The perspective for the vertical green spaces as an important part of the holistic approach to the decarbonization and urban green transition is discussed in the light of the New European Bauhaus. The purpose of this study is to present a comparative review of vertical green façades with the perspective of their thermal performance. The authors highlight the energy saving potential of vertical green systems for different spatial, structural and bioclimatic solutions. Moreover, as a result of this review, the authors explain the parameters that designers should consider for achieving the best thermal performance of a vertical green system. The paper also analyses the pros and cons of the application of movable green panels.
Keywords: vertical green façades; movable green panels; energy efficient cities; New European Bauhaus; pionowe zielone elewacje; ruchome zielone panele; miasta energooszczędne; Nowy Europejski Bauhaus